2016
DOI: 10.1016/j.micpath.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid transporter NanT participates in Tannerella forsythia biofilm formation and survival on epithelial cells

Abstract: Tannerella forsythia is a periodontal pathogen implicated in periodontitis. This gram-negative pathogen depends on exogenous peptidoglycan amino sugar N-acetylmuramic acid (NAM) for growth. In the biofilm state the bacterium can utilize sialic acid (Neu5Ac) instead of NAM to sustain its growth. Thus, the sialic acid utilization system of the bacterium plays a critical role in the growth and survival of the organism in the absence of NAM. We sought the function of a T. forsythia gene annotated as nanT coding fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In this regard, the periodontal pathogen T. forsythia , which is found in close association with F. nucleatum in dental plaque [1], could harvest sialic acid from F. nucleatum LPS. Our previous studies have indicated that utilization of sialic acid from host and cohabiting bacterial partners such as fusobacteria likely plays a role in the survival of T. forsythia in the oral environment [26]. The identification of FucNAc4N is of interest as this monosaccharide is often found, as it is here, as a component of zwitterionic polysaccharides that may have biological implications [27, 28].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the periodontal pathogen T. forsythia , which is found in close association with F. nucleatum in dental plaque [1], could harvest sialic acid from F. nucleatum LPS. Our previous studies have indicated that utilization of sialic acid from host and cohabiting bacterial partners such as fusobacteria likely plays a role in the survival of T. forsythia in the oral environment [26]. The identification of FucNAc4N is of interest as this monosaccharide is often found, as it is here, as a component of zwitterionic polysaccharides that may have biological implications [27, 28].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, metabolic pathways exist in some bacteria that allow them to direct sialic acid into peptidoglycan synthesis . As mentioned above, although sialic acid is nutritionally important for the growth of T. forsythia in biofilms, sialic acid utilization is also critical for the survival of T. forsythia on epithelial cells . It was observed that, compared with the parental strain, a sialic acid transport‐deficient mutant was significantly less fit to survive on oral epithelial cell monolayers .…”
Section: Scavenging On Host Sialic Acid For Survival In Biofilmsmentioning
confidence: 99%
“…[48][49][50][51][52][53] As mentioned above, although sialic acid is nutritionally important for the growth of T. forsythia in biofilms, 47 sialic acid utilization is also critical for the survival of T. forsythia on epithelial cells. 54 It was observed that, compared with the parental strain, a sialic acid transport-deficient mutant was significantly less fit to survive on oral epithelial cell monolayers. 54 Not only epithelial cells, but other bacteria with which T. forsythia is known to interact, such as F. nucleatum can provide sialic acid.…”
Section: Scavenging On Host Sialic Acid For Survival In Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homologues of NanT are found throughout a wide range of human pathogens within the Enterobacteriaceae including the genera Salmonella, Yersinia, Citrobacter and Chronobacter [12] , but none of these have been experimentally characterised. Homologues are also seen in the Bacteroidetes which have been studied including the NanT protein in the oral pathogen Tannerella forsythia by the Stafford group [13,14] , who have also demonstrated a role for sialic acid uptake for biofilm formation and also survival when exposed to epithelial cells in this organism [14] . A role for NanT in sialic acid uptake has also been demonstrated in the closely related gut bacterium Bacteroides fragilis [15] .…”
Section: Introductionmentioning
confidence: 99%